2-Arylacetamido-4-phenylamino-5-substituted pyridazinones as formyl peptide receptors agonists. Issue 11 (1st June 2016) - Vergelli, Claudia; Schepetkin, Igor A.; Ciciani, Giovanna; Cilibrizzi, Agostino; Crocetti, Letizia; Giovannoni, Maria Paola; Guerrini, Gabriella; Iacovone, Antonella; Kirpotina, Liliya N.; Khlebnikov, Andrei I.; Ye, Richard D.; Quinn, Mark T.
Graphical abstract: Active as FPR agonists in the low micromolar range. Abstract: N -Formyl peptide receptors (FPRs: FPR1, FPR2, and FPR3) are G protein-coupled receptors that play key roles in modulating immune cells. FPRs represent potentially important therapeutic targets for the development of drugs that could enhance endogenous anti-inflammation systems associated with various pathologies, thereby reducing the progression of inflammatory conditions. Previously, we identified 2-arylacetamide pyridazin-3(2 H )-ones as FPR1- or FPR2-selective agonists, as well as a large number of FPR1/FPR2-dual agonists and several mixed-agonists for the three FPR isoforms. Here, we report a new series of 2-arylacetamido-4-aniline pyridazin-3(2 H )-ones substituted in position 5 as a further development of these FPR agonists. Chemical manipulation presented in this work resulted in mixed FPR agonists8a, 13a and27b, which had EC50 values in nanomolar range. In particular, compound8a showed a preference for FPR1 (EC50  = 45 nM), while13a and27b showed a moderate preference for FPR2 (EC50  = 35 and 61 nM, respectively). Thus, these compounds may represent valuable tools for studying FPR activation and signaling.